2023
DOI: 10.15376/biores.18.1.1714-1730
|View full text |Cite
|
Sign up to set email alerts
|

Activation temperature and particle size of palm kernel shell vs. the surface properties of activated carbon

Abstract: Granular activated carbon (GAC) and powdered activated carbon (PAC) are the two most common forms of activated carbon with varying particle size range. The goal of this study was to analyze the key factors (particle size and activation temperature) affecting the surface characteristics of GAC and PAC derived from palm kernel shell (PKS). The surface morphology suggested that the pore network in PKS-PAC is more developed than that in PKS-GAC owing to the presence of a micropore structure when prepared at lower … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 50 publications
(57 reference statements)
0
1
0
Order By: Relevance
“…Research by Andas et al and Lee et al [69,70] found that PKS-based activated carbon generated by two-step activation process had an extensive surface area and excellent methylene blue dye adsorption capability. The research also revealed that the properties of the activated carbon that was produced were greatly impacted by the activation procedure.…”
Section: Biomass In Malaysia For Ac Productionmentioning
confidence: 99%
See 2 more Smart Citations
“…Research by Andas et al and Lee et al [69,70] found that PKS-based activated carbon generated by two-step activation process had an extensive surface area and excellent methylene blue dye adsorption capability. The research also revealed that the properties of the activated carbon that was produced were greatly impacted by the activation procedure.…”
Section: Biomass In Malaysia For Ac Productionmentioning
confidence: 99%
“…The possible application of different kinds of biomass precursors, including PKS, for the production of activated carbon in Malaysia was covered by Andas et al, Lee et al, and Zainal et al [67,69,70]. PKS, according to the researchers, is an appropriate precursor for the creation of activated carbon because of its high carbon concentration and minimal ash content.…”
Section: Biomass In Malaysia For Ac Productionmentioning
confidence: 99%
See 1 more Smart Citation
“…Palm kernel shell graphene oxide samples were prepared by Institute of Tropical Forestry and Forest Products, University Putra Malaysia. The detailed description of the synthesis of the material was previously described by [39][40][41]. Differences in synthesis procedure for all samples are highlighted in Table 2.…”
Section: Reagentsmentioning
confidence: 99%